(untitled) (Experimental biology, 2023)
Research work on the identification of the species composition of the mycobiota of the Ural Valley within the West Kazakhstan region was carried out in the forest communities of the region from 2019 to 2022. This article presents data on the first find of Amanita vittadinii (Moretti) Vittad. in the study area. Based on field studies, a new habitat of the saprotrophic cap mushroom Amanita vittadinii (Moretti) Vittad was first discovered. Previously not marked for this region and being a geographical novelty. The article describes the macro and micromorphometric characteristics of the find, its locations and natural complexes in the places of growth of the species, and a geobotanical description of the main forest-forming and meadow-forming communities was also carried out. Previously, this species was known only in the southern regions of the country, and even there it is little studied from a mycological point of view, and the information there is haphazard and fragmentary. And in the valley of the Ural River, this species is one of the unexplored species. However, it is known that the object of study occupies a large place in the ecosystem and is an active part of the reducent system. We believe that the information presented in the article is of value not only for the Ural River valley, but also for assessing the overall mycofloric diversity of the country.